Pengaruh Budaya Organisasi dan Gaya Kepemimpinan Path Goal Theory Terhadap Perkembangan Karir Tenaga Pendidik - Pujiantari, Roni; Badrun, Badrun; Fitriani, Mohamad Iwan (STAI Darul Kamal NW Kembang Kerang, 2024)
The purpose of the study is to invertigate whether there is an influence of organizational culture and path goal theory leadership style on the career development of educators in the Central Lombok Education Office. This study comprises three variables: organization culture (X1), path goal theory leadership style (X2) as independent variables, and career development of educators as the dependent variabel (Y). The study conducted a quantitative approach with 110 population of teachers, with a sample size of 84 teachers selected using cluster random sampling. The data collection was performed using an instrument that has been validated and tested for its realiability. Furthermore, the collected data was subjected to pre-requisite tests for normality, linearity, and multicollinearity. The hypothesis testing employed in this study included the F-test, which is a simultaneous test, and the T-test, which is a partial test, both analyzaed using SPSS 16.0 software. The findings of the study demonstrate that: (1) Organizational culture has a partial effect on the career development of educators in the Central Lombok Education Office. (2) Path-Goal Theory leadership style has an effect on the career development of educators in the Central Lombok Education Office. Meanwhile, a simultaneous have been effect.